Marketing mix and customer satisfaction of gyms and fitness clubs in Malaysia: a conceptual paper - Zurina Patrick; Nornajihah Nadia Hasbullah; Ribed Vianneca W. Jubilee; Andrew Tek Wei Saw; Norfadzila Patrick (Human Resource Management Academic Research Society (HRMARS), 2022)
Customer satisfaction is a major concern in every organization, including fitness. The fitness industry has grown steadily as consumers seek a healthier lifestyle and a more productive workout environment. The 7Ps marketing mix is considered a crucial determinant of consumer satisfaction. Understanding what influences customer satisfaction is critical to measuring and managing it in gyms and fitness clubs. This study focuses on the 7Ps marketing mix: product, price, place, promotion, people, physical evidence, and process. The conceptual framework includes theoretical framework and hypotheses development, research methodology, research implication, conclusion, as well as limitation and further research. Through the understanding of these factors, the researchers aim to show a better understanding of the 7Ps marketing mix concept and the factors that affect the customer satisfaction of gyms and fitness clubs in Malaysia.